Beispiel Nr: 15
$ \text{Gegeben:} \\ a1 \cdot x + b1\cdot y + c1\cdot z=d1\\ a2\cdot x + b2\cdot y + c2\cdot z=d2\\ a3\cdot x + b3\cdot y + c3\cdot z=d3\\ \\ \text{Gesucht:} \\\text{x,y,z} \\ \\ \textbf{Gegeben:} \\ 1 x -2 + 3 z=9\\ 3 x +8 y + 9 z=5\\ 2 x +3 y + 6 z=7\\ \\ \\ \textbf{Rechnung:} \\ 1 x + -2 y + 3 z=9\\ 3 x +8 y +9 z=5\\ 2 x +3 y +6 z=7\\ D_h=\left|\begin{array}{ccc} 1\ & -2 & 3\\ 3&8 & 9\\ 2& 3 & 6 \\ \end{array}\right| \begin{array}{cc} 1\ & -2 \\ 3&8 \\ 2& 3 \end{array} \\ D_h=1 \cdot 8 \cdot 6+\left(-2\right) \cdot 9 \cdot 2 +3 \cdot 3 \cdot 3 - 3 \cdot 8 \cdot 2 -1 \cdot 9 \cdot 3 -\left(-2\right) \cdot 3 \cdot 6=0 \\ D_x=\left|\begin{array}{ccc} 9\ & -2 & 3\\ 5&8 & 9\\ 7& 3 & 6 \\ \end{array}\right| \begin{array}{cc} 9\ & -2 \\ 5&8 \\ 7& 3 \end{array} \\ D_x=9 \cdot 8 \cdot 6+ \left(-2\right) \cdot 9 \cdot 7 +3 \cdot 5 \cdot 3 - 3 \cdot 8 \cdot 7 - 9 \cdot 9 \cdot 3 -\left(-2\right) \cdot 5 \cdot 6=0\\ D_y=\left|\begin{array}{ccc} 1\ & 9 & 3\\ 3&5 & 9\\ 2& 7 & 6 \\ \end{array}\right| \begin{array}{cc} 1\ & 9 \\ 3&5 \\ 2& 7 \end{array} \\ D_y=1 \cdot 5 \cdot 6+9 \cdot 9 \cdot 2 +3 \cdot 3 \cdot 7 - 3 \cdot 5 \cdot 2 -1 \cdot 9 \cdot 7 -9 \cdot 3 \cdot 6=0 \\ D_z=\left|\begin{array}{ccc} 1\ & -2 & 9\\ 3&8 & 5\\ 2& 3 & 7 \\ \end{array}\right| \begin{array}{cc} 1\ & -2 \\ 3&8 \\ 2& 3 \end{array} \\ D_z=1 \cdot 8 \cdot 7+\left(-2\right) \cdot 5 \cdot 2 +9 \cdot 3 \cdot 3 - 9 \cdot 8 \cdot 2 -1 \cdot 5 \cdot 3 -\left(-2\right) \cdot 3 \cdot 7=0\\ \\ L= unendlich$